ETICA ECONOMICA E CREDITO NELLA SUMMA ASTESANA (1317): Appunti sul pensiero teologico-sociale francescano nel I° sec. di vita - Bazzichi, Oreste (Miscellanea francescana, 2018)
The Franciscan friar Astesano of Asti, in continuing the socio-economic tradition of the preceding confreres, wrote in 1317 the Summa de casibus coscientiae, also known as the Summa Astesiana or Astensis. It describes great fortune and was widespread, as witnessed by the many editions that occurred over three centuries throughout Europe. The success is due to the fact that, residing in the Franciscan friary of Asti (built around 1228) as the fi nal turning point of the merchants' technique, and then, starting from Genoa, money fl ooded every part of Europe. He sensed the need to write a vademecum (a manual, giving life to the beginning of the handbooks) on the monetary, credit and exchange policy to offer confessors an informative and evaluation instrument in the internal forum. Following the activity of the campsor, Astesano, as a practical canonist, analyzed the source of the correct value in monetary exchange rates, land rent ad vitam ementis, accelerative selling, the anticipation of payments, corporate lending, purchases and life annuities, as well as in many and detailed forms of contracts. The Summa Astesiana was not amended, probably because of its size, speculative and canonistic character. Other than Angelo Carletti from Chivasso and Battista di Trovamala di Sale, we must remember Saint Bernardine of Siena who was among those who drew upon it. Finally, the success of the Astesano is also linked to the history of the compilation of dictionaries on Law. The title 41 De signifi catione verborum of the last book of the Summa constitutes the only non-anonymous legal vocabulary of a long series produced by the schools of the Late Middle Ages, especially German. (English)